Design and Usability of the Next Medical Devices for the Home Care. (28th July 2017) - Tosi, Francesca; Rinaldi, Alessandra
Abstract: The growing complexity of instruments for health care and of medical devices for personal use has led to an intensification of the risks related to bad functioning and failure to function or misunderstanding how to use the interface, control and adjustment elements etc. Besides, the general tendency to reduce hospitalisation to the minimum by transferring many of the patient's care stages at home has led to the involvement of "non experts". It follows that radical rethinking is required of the subjects involved, who will actually use the medical devices to care for and assist the patient. Ergonomics in Design and Design strategies to orientate the design of new products and to satisfy the needs of the plurality of user profiles involved in home care. This article presents part of the results of the research and experimentation performed by Florence University Laboratory of Ergonomics and Design.